Characteristics constituents with antidiabetic significance from Indian mangrove apples - Avijit Saha; Tapan Seal; Shuvam Saha; Alok Hazra; Sandip Ghosh; Tapas Sur (Shahrekord University of Medical Sciences, 2023)
Background and aims: There is limited information on the chemical nature of the edible fruits of the mangrove Sonneratia apetala, which is utilized in traditional medicine in coastal areas. The goal of the current research was to identify the biologically active substances behind their therapeutic effects, particularly blood sugar regulation. Methods: To determine the chemical fingerprint of S. apetala fruit extract, reversed phase high performance liquid chromatography (RP-HPLC) and gas chromatography-mass spectrometry (GC-MS) profiling were used. The antioxidant properties were thoroughly examined. α-Amylase and α-glucosidase enzymes were also used to evaluate the impact of S. apetala fruit extract on the regulatory mechanism for the metabolism of carbohydrates. Results: S. apetala fruit extract showed high concentrations of phenolics, flavonoids, and water-soluble vitamins (C, B2, B5, and B6). Quercetin, catechin, rutin, myricetin, p-coumaric acid, ferulic acid, gallic acid, sinapic acid, and ascorbic acid were among the recognized therapeutically active substances found in RP-HPLC. The presence of β-amyrin and lupeol in S. apetala fruit extract was determined by the GC-MS profile. The carbohydrate-slitting enzymes α-amylase and α-glucosidase were also strongly inhibited by S. apetala fruit extract. Conclusion: The fruit of S. apetala contains therapeutically useful polyphenolics, triterpenoids, phytosterols, and vitamins. It can lower blood sugar absorption by blocking enzymes that break down carbohydrates and has potent antioxidant qualities.